Nutrient requirements and low-cost balanced diets, based on seasonally available local feedstuffs, for local pigs on smallholder farms in western Kenya - Carter, Natalie A.; Dewey, Catherine E.; Thomas, Lian F.; Lukuyu, Ben A.; Grace, Delia; Lange, C.F.M. de (Springer, 2016)
Growth performance of pigs on smallholder farms in the tropics is low. Lack of feedstuffs, seasonal feed shortages, and feeding nutritionally unbalanced diets contribute to slow growth. Low-cost balanced diets are needed to improve pig performance. In this study, we estimated the nutrient requirements of local pigs on smallholder farms in Kenya and developed balanced low-cost diets using seasonally available local feedstuffs. Diets were formulated to provide pigs with 80 % of the nutrient density in corn and soybean meal-based (reference) diets to minimize the cost per unit of energy and other nutrients. Estimated requirements for starting and growing pigs (8 to 35 kg body weight) were as follows: digestible energy (DE) 2960 kcal/kg of dry matter (DM), standardized ileal digestibility (SID) lysine 5.8 g/kg of DM, calcium 2.8 g/kg of DM, standardized total tract digestible (STTD) phosphorous 1.4 g/kg of DM, and crude protein 85 g/kg of DM. Nutrient requirements of local pigs on smallholder farms in Kenya were lower than those of exotic breed pigs raised in commercial settings. Seasonally available local feedstuffs were used to develop low-cost balanced diets. Twenty-two diets are presented based on season, cost, and feedstuff availability. This study has broad applicability as a case study of an approach that could be applied in other tropical regions in which smallholder pig keeping is practiced and where local feedstuffs for pigs are available seasonally.